Preparation and catalytic performance of alginate-based Schiff Base. (15th March 2019) - Wang, Lianxu; Hou, Yaheng; Zhong, Xin; Hu, Jianglei; Shi, Fengwei; Mi, Haoyu
Highlights: Novel alginate-based Schiff Base Cu (II) complex was prepared. The content of stablized metal of alginate-based Schiff Base was improved by 1.3 times. Relation between degree of oxidation and stabilized metal content of alginate was illustrated. Abstract: As a biomass polymer, alginate-based material has drawn considerable attention and been applied in many fields. However, the research on alginate-based Schiff Base metal complex is scarce. Herein, a novel alginate-based Schiff Base Cu (II) complex was prepared via oxidation and imidization of alginate by periodate and organic amine, respectively. In additon, their catalytic performance in phenol hydroxylation reaction was investgated. Results illustrated that degree of oxidation had significant influence on metal loaded content. Compared with alginate, the alginate-based Schiff Base has more reactive groups, and can stablize more Cu cations which endowed their better catalytic activities.